2006
DOI: 10.1029/2006jf000477
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the geomorphically effective event for fluvial processes over long periods

Abstract: [1] Fluvial processes erode landscapes in response to a wide range of discharges. The importance of a given discharge to the erosion of a basin can be calculated by multiplying the discharge's frequency of occurrence and the erosion rate produced by the discharge. The discharge that contributes the most geomorphic work is called the geomorphically effective event (GEE). In this paper, the behavior of the GEE is examined when a generic stream power model with a threshold is used to describe either the detachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Willgoose et al (1989) justifi ed this approach by deriving a time-averaged sediment transport equation based on the Einstein-Brown formula (see Julien (1998)) in which the applicable discharge is the mean annual peak discharge; however, because some terms were discarded, the result is approximate rather than exact unless the discharge exponent is an integer. Huang and Niemann (2006) analysed the return period of the geomorphically effective event under a range of erosion laws and catchment states, and found that in general the event return period -and thus its intensity -varied systematically throughout the network in most cases. Several studies have explored the role of discharge variability in time (Willgoose, 1989;Tucker and Bras, 2000;Molnar, 2001;Tucker, 2004;Molnar et al, 2006;Lague et al, 2005).…”
Section: Geomorphically Effective Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Willgoose et al (1989) justifi ed this approach by deriving a time-averaged sediment transport equation based on the Einstein-Brown formula (see Julien (1998)) in which the applicable discharge is the mean annual peak discharge; however, because some terms were discarded, the result is approximate rather than exact unless the discharge exponent is an integer. Huang and Niemann (2006) analysed the return period of the geomorphically effective event under a range of erosion laws and catchment states, and found that in general the event return period -and thus its intensity -varied systematically throughout the network in most cases. Several studies have explored the role of discharge variability in time (Willgoose, 1989;Tucker and Bras, 2000;Molnar, 2001;Tucker, 2004;Molnar et al, 2006;Lague et al, 2005).…”
Section: Geomorphically Effective Eventsmentioning
confidence: 99%
“…In fact, there are many fascinating and unanswered questions regarding the feedbacks between climate, hydrology and landscape evolution. While models of drainage basin evolution have begun to address some of these, including issues of both precipitation distribution and phase (Beaumont et al, 1992;Roe et al, 2002;Anders et al, 2008) as well as runoff generation (Sólyom and Tucker, 2004;Huang and Niemann, 2006), the topography-hydrology-climate connection remains a rich problem to be explored.…”
Section: Geomorphic Transport Functions For Hillslope Processesmentioning
confidence: 99%
“…Hence, the derived shape of hypsometric curves gives in for ma tion about the vol ume of orig i nal ba sin re mains, and in di cates an ero sional stage of drain age bas ins as out come of in ter ac tion be tween tectonic ac tiv ity, lithological het er o ge ne ity and cli ma tic con di tions (Willgoose and Han cock, 1998;Huang and Niemann, 2006). Keller and Pinter (2002) sug gested that hypsometric curves can be used for com par ing drain age bas ins of dif fer ent size and can be used to sep a rate phases in land scape evo lu tion.…”
Section: Hypsometric Curvesmentioning
confidence: 99%
“…For example, the assumption that flow may be parameterized as a function of upslope contributing area is inappropriate in semi-arid environments, where localized storms are mismatched with the area of the catchment. In addition, the assumption that erosion is driven by a single, representative discharge is flawed; numerous studies have demonstrated that assumptions of a single discharge produce different results compared with a range of discharges (Wainwright & Parsons, 1998;Zhang et al, 2002;Huang & Niemann, 2006).…”
Section: Statistical Scaling In Simple Conditionsmentioning
confidence: 99%